Efektivitas Penggunaan E-Modul Dalam Meningkatkan Perilaku Afektif Dan Critical Thinking Skill Mata Pelajaran PPKN di SMPN 1 Bangkalan - Trimurtiningsih, Anni; Eka, Soesiana Tri; Hanifah, Sri Yuni (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
Technology and conditions of distance learning, one of the learning media that can be used is the use of electronic modules (e-modules) which are present as an adaptive form of ordinary modules used during direct learning. "E-modules are expected to become a new learning resource for students which in turn is expected to improve understanding of concepts and learning outcomes." The aim of this research is to determine the effectiveness of using e-modules in improving affective behaviour and critical thinking skills in Civics subjects at SMPN 1 Bangkalan? By using a quantitative approach, the type of research used is experimental research. The results of calculations with the help of SPSS obtained the percentage of influence between variables, the effectiveness of the e-module had a percentage of 13.7% on the affective behaviour of experimental class students, meaning that the increase in students' affective behavior was 13.7% influenced by the e-module implemented by researchers in the experimental class. Meanwhile, in the next table, e-modules have an influence of 40.4% on students' critical thinking skills in the experimental class. This means that when researchers implemented e-modules in experimental classes, 40.4% of students' critical thinking skills during the learning process were influenced by e-modules. so that it can provide solutions to students' problems in learning, so that teachers can use this research as an alternative learning method.